2020
DOI: 10.3164/jcbn.20-89
|View full text |Cite
|
Sign up to set email alerts
|

Walnut polyphenol extracts inhibit <i>Helicobacter pylori</i>-induced STAT3<sup>Tyr705</sup> phosphorylation through activation of PPAR-γ and SOCS1 induction

Abstract: The health beneficial effects of walnut plentiful of n 3 polyunsatu rated fatty acid had been attributed to its anti inflammatory and anti oxidative properties against various clinical diseases. Since we have published Fat 1 transgenic mice overexpressing 3 desaturase significantly mitigated Helicobacter pylori (H. pylori) associated gastric pathologies including rejuvenation of chronic atrophic gastritis and prevention of gastric cancer, in this study, we have explored the underlying molecular mechanisms of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…This is an extended study of previous publication that walnut polyphenol extract (WPE) significantly ameliorated H. pylori -associated inflammation through sequential actions of PPAR-γ activation, SOCS-1 induction, IL-6/gp130 inhibition, and STAT3 inactivation. ( 8 ) Translating these in vitro actions of WPE, in the current study, we documented that dietary intake of walnut could significantly ameliorate gastric inflammation, significantly rejuvenate CAG, and mitigate gastric carcinogenesis via concerted actions of attenuated inflammatory mediators, increased preservation of 15-PGDH, and enhanced gastric defense mechanisms (Fig. 8 ).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This is an extended study of previous publication that walnut polyphenol extract (WPE) significantly ameliorated H. pylori -associated inflammation through sequential actions of PPAR-γ activation, SOCS-1 induction, IL-6/gp130 inhibition, and STAT3 inactivation. ( 8 ) Translating these in vitro actions of WPE, in the current study, we documented that dietary intake of walnut could significantly ameliorate gastric inflammation, significantly rejuvenate CAG, and mitigate gastric carcinogenesis via concerted actions of attenuated inflammatory mediators, increased preservation of 15-PGDH, and enhanced gastric defense mechanisms (Fig. 8 ).…”
Section: Discussionmentioning
confidence: 51%
“…Among dietary intervention as non-microbial or dietary approach targeted for H. pylori infection, quite several agents had been studied, including blueberry plants, ( 3 ) phytochemicals from fruits, ( 4 ) genistein from soy rich diet, ( 5 ) dietary antioxidant β-carotene or astaxanthin, ( 6 , 7 ) and n -3 polyunsaturated fatty acids ( n -3 PUFAs)-rich walnut. ( 8 ) Stimulated with significant cancer preventive outcome of walnut that n -PUFAs synthesizing Fat -1 transgenic mice synthesizing n -3 PUFAs such as DHA or EPA significantly resisted from chronic H. pylori -associated gastric carcinogenesis and walnut polyphenol extracts significantly inhibited interleukin-6 (IL-6)/Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) signaling via peroxisome proliferator-activated receptor γ (PPAR-γ)/suppressors of cytokine secretion (SOCS) 1 stimulation in gastric cells, ( 8 , 9 ) we put hypothesis that dietary intake of walnut ( Juglans regia L.) can reduce H. pylori -associated gastric carcinogenesis. In this study, we have explored the efficacy of dietary intake of walnut against H. pylori -associated chronic atrophic gastritis (CAG) or gastric cancer model and extended documentation the molecular pathologic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory function of resveratrol and epicatechin on IL-8 is probably related to their inhibitory activity on the NF-κB pathway, which downregulates the expression level of IL-8. Research has found that Walnut polyphenol extracts prevent Hp -related tumor growth by inhibiting STAT3 phosphorylation and nuclear translocation in gastric mucosal cells [ 63 ], and reversing precancerous atrophic gastritis [ 64 ]. Nobiletin has been confirmed to inhibit Hp infection and prevent Hp -mediated GC [ 65 ].…”
Section: Polyphenols Protect Indirectly From Gc By Inhibiting ...mentioning
confidence: 99%
“…The beneficial health effects of walnut have long been attributed to its rich n-3 polyunsaturated fatty acid character and anti-oxidative and anti-inflammatory properties. In a study by Park et al, 10 or 20 µg/mL walnut polyphenol extracts were found to suppress H. pylori infection induced phosphorylation of STAT3 in a PPAR-γ dependent manner in RGM-1 gastric mucosal cells, thereby providing protection against gastric pathologies such as chronic atrophic gastritis and gastric cancer [43]. Moreover, Hossen et al found that 50 µM resveratrol extract exerted anti-inflammatory effects on lipopolysaccharide-treated macrophages by inhibiting the signaling events upstream of NF-κB translocation such as phosphorylation of AKT and the formation of PDK1-AKT signaling complexes [44].…”
Section: Digestive Diseasesmentioning
confidence: 99%